2016
DOI: 10.1038/npjamd.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative phosphorylation in response to acute and chronic DNA damage

Abstract: Accumulation of DNA damage is intricately linked to aging, aging-related diseases and progeroid syndromes such as Cockayne syndrome (CS). Free radicals from endogenous oxidative energy metabolism can damage DNA, however the potential of acute or chronic DNA damage to modulate cellular and/or organismal energy metabolism remains largely unexplored. We modeled chronic endogenous genotoxic stress using a DNA repair-deficient Csa−/−|Xpa−/− mouse model of CS. Exogenous genotoxic stress was modeled in mice in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 43 publications
4
75
0
Order By: Relevance
“…In work by Huang et al irinotecan treatment increased ROS generation in two human colorectal cancer cell lines, and this promoted apoptosis and reduced cell viability (29). Irinotecan elevated fatty acid oxidation (FAO) capacity in mouse tissues (liver and muscle) after treatment (30), and this effect was considered to be a common response to the increased energy demands when under genotoxic stress (because FAO provides reducing equivalents-NADH, FADH 2 , for efficient ATP generation via mitochondrial OXPHOS).…”
Section: Discussionmentioning
confidence: 99%
“…In work by Huang et al irinotecan treatment increased ROS generation in two human colorectal cancer cell lines, and this promoted apoptosis and reduced cell viability (29). Irinotecan elevated fatty acid oxidation (FAO) capacity in mouse tissues (liver and muscle) after treatment (30), and this effect was considered to be a common response to the increased energy demands when under genotoxic stress (because FAO provides reducing equivalents-NADH, FADH 2 , for efficient ATP generation via mitochondrial OXPHOS).…”
Section: Discussionmentioning
confidence: 99%
“…Through either direct interaction or via poly (ADP-ribose) (PAR) polymer formation PARP1 can modulate the activity of ataxia-telangiectasia mutated kinase (ATM) [23] and tumor suppressor protein 53 (p53) [24,25] involved in DNA damage response. Enhanced PARP1 activity also induces ATP depletion [26], which implies the activation of AMPK-activated protein kinase (AMPK) [27,28] that is responsible for the regulation of various cellular pathways including protein kinase B (AKT) and mammalian target of rapamycin (mTOR) [29][30][31]. This complex interplay between PARP1, ATM, AMKP, p53, AKT, and mTOR indicates that these DNA damage responders can fine-tune and modulate the interaction between DNA repair pathways with metabolism [32].…”
mentioning
confidence: 99%
“…Studies using UVC irradiation revealed that UVC induced mitochondrial hyperfusion and resulted in enhanced ATP synthesis via oxidative phosphorylation (OXPHOS) [50]. Other authors demonstrated that UVC irradiation caused a significant increase in mitochondrial content, oxygen consumption, and fatty acid oxidation [28]. Nevertheless, the functional consequences of mitochondrial alterations after UVB-induced DNA damage and the molecular pathways leading to mitochondrial changes remain to be elucidated.…”
mentioning
confidence: 99%
“…Otherwise, due to energy drop, it induces necrosis [3]. However, recent findings underline that an adaptive metabolism can occur, with a stimulation of AMPK (AMP-activated protein kinase), leading to an increase in fatty acid oxidation (FAO) and oxidative phosphorylation (OXPHOS) following DNA damage and PARP-1 activation [2] (Figure 1). …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The impact of DNA damage and its impact on energy metabolism was firstly evidenced with the DNA damage sensor PARP-1 (poly(ADP-ribose) polymerase 1) [2]. Activated by numerous genotoxic stresses (by physical or chemical agents, upon acute or chronic exposure), PARP-1 triggers ATP and NAD + depletions, associated by mitochondrial depolarization, reactive oxygen species (ROS) production and apoptosis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%